Beelden van stilte : Bosnië. - Seresia, Marijke; Detrez, Raymond; Van den Abeele, Charlotte (Antwerpen : Gynaika)
Dalemans, Mine ; Donckers, Monique ; Garmendia, Cuauhtemoc ; Horozic, Jasmin ; Membrandt ; Seresia, Marijke ; Sisic, Sahin ; Tricnon, Claudia ; Van Alsenoy, Aldegonde ; Vrancken, Tanja ; Wintmolders, Kristien
boek